2020
DOI: 10.3390/ma13204587
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Porosity and Biocidal Properties of the Chitosan-Hyaluronate Matrix Hydrogel Nanocomposites by the Addition of 2D Ti3C2Tx MXene

Abstract: A recent discovery of the unique biological properties of two-dimensional transition metal carbides (MXenes) resulted in intensive research on their application in various biotechnological areas, including polymeric nanocomposite systems. However, the true potential of MXene as an additive to bioactive natural porous composite structures has yet to be fully explored. Here, we report that the addition of 2D Ti3C2Tx MXene by reducing the porosity of the chitosan-hyaluronate matrix nanocomposite structures, stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…In another study, 2D Ti 3 C 2 T x MXene flakes were prepared and incorporated into a chitosan‐hyaluronate (CH/SHA/Ti 3 C 2 T x ) matrix. [ 39 ] The impact of a composite containing varying concentrations of MXene was investigated using three bacterial strains, i.e., gram‐negative E. coli , gram‐positive S. aureus , and Bacillus sp . The results showed that the biocidal property of the nanocomposites with varying amounts of MXene depended on the type of bacteria.…”
Section: Infection Therapymentioning
confidence: 99%
“…In another study, 2D Ti 3 C 2 T x MXene flakes were prepared and incorporated into a chitosan‐hyaluronate (CH/SHA/Ti 3 C 2 T x ) matrix. [ 39 ] The impact of a composite containing varying concentrations of MXene was investigated using three bacterial strains, i.e., gram‐negative E. coli , gram‐positive S. aureus , and Bacillus sp . The results showed that the biocidal property of the nanocomposites with varying amounts of MXene depended on the type of bacteria.…”
Section: Infection Therapymentioning
confidence: 99%
“…The weight gain for the 8 BL coating of PUF was only 6.9% because to the use of ultra-thin Ti 3 C 2 nanosheets, which minimized the negative influence on the intrinsic attributes of PUF. PUF’s flammability and smoke emissions were dramatically reduced by the Ti 3 C 2 /chitosan coating [ 69 ].…”
Section: Polysaccharide Composites Encompassing Mxenementioning
confidence: 99%
“… SEM and micro-CT images for the ( A , E ) reference CH/SHA matrix nanocomposite and modified with ( B , F ) 1 wt.%, ( C , G ) 5 wt.% and ( D , H ) 10 wt.% of 2D Ti 3 C 2 T x MXene lakes [ 69 ]. …”
Section: Figurementioning
confidence: 99%
“…To improve antibacterial functionality, CS films are usually deposited as composites, combining chitosan with inorganic and metallic particles [ 2 , 14 , 15 , 16 , 17 , 18 ]. The best antibacterial performance has been achieved for the CS–silver nanoparticle (AgNP) composites [ 16 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%